Modified pectins with activity against colon cancer: A systematic review from 2010-2021 - Matías Pérez-Loyola; Marisela Valdés-González; Gabino Garrido (GarVal Editorial Ltda., 2022)
Context: Colon cancer is a serious disease that can be hereditary or arise from exposure to carcinogens in unhealthy food. Current chemotherapy treatment has serious cardiovascular adverse effects, is not always effective, and there may be resistance to treatment. Recently, studies have found an optimal anticancer activity of modified pectins on colon cancer. Aims: To systematically review the scientific literature, with PRISMA guidelines, of the articles found in the last 11 years, on the potential anticancer effects of pectins on colon cancer. Methods: PRISMA and Rayyan were used for the selection of studies and a standardized search was followed in four databases with the terms: modified pectins, cancer, therapy. Data extraction was performed using Excel and relevant information on anticancer activity was collected. Results: In total, 16 articles were included, finding seven in vitro, three mixed and six in vivo studies. The anticancer activity and optimization of the formulation, encapsulation, release of pectin-based drugs were evaluated by different methods in 12 and six articles, respectively. Most of the studies were classified as high quality with the AXIS tool. Furthermore, 11 out of 12 articles showed positive effects of modified pectins on colon cancer both in vivo and in vitro and six out of six articles found positive effects on pectin-based formulations. Conclusions: The evidence found suggests a beneficial effect of modified pectins on colon cancer, however, more in vivo studies are required.